2019
DOI: 10.14569/ijacsa.2019.0101153
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to the Success of Information Security Management Implementation

Abstract: Information Security Management (ISM) concerns shielding the integrity, confidentiality, availability, authenticity, reliability and accountability of the organisation's information from unauthorised access in order to ensure business continuity and customers' confidence. The importance of information security (IS) in today's situation should be given due attention. Recognising its importance, organisations nowadays have devoted wide efforts in protecting their information. They establish information security … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The data collected from the survey were analysed using Statistical Analysis. The findings of this empirical II have been reported in [60].…”
Section: B Phase2: Empiricalmentioning
confidence: 66%
“…The data collected from the survey were analysed using Statistical Analysis. The findings of this empirical II have been reported in [60].…”
Section: B Phase2: Empiricalmentioning
confidence: 66%
“…The finding of the study coincide that of Alotaibi & Almagwashi (2018) who found that in order to implement information system security awareness there are cost need to be incurred that is material and technology cost needs money, the study collaborate that of Alghamdi et al (2020) who found cost in changing organization culture, because after awareness program the organization culture should change to become with security change as is found in ISG framework. Zammani et al (2019) argued that there is no motivation towards awareness of latest security policy, threats and issues that occur in the organization hence cost of awareness programs is to ensure the employees, third parties and stakeholders are aware of IS policy, IS issues and IS threats as well as their responsibilities in protecting the organization's information is needed. Zaslavskiy et al (2018) found challenge that some stakeholders are not aware of specific threats to the cloud infrastructure, hence there is a need to take measures to detect threats and avoid them before they occur, Also according to Alotaibi et al (2018) there is a challenge in both information security technology and human factor awareness and many organization concentrate mainly on technology awareness and weaken human factor awareness which is considered as the weakest link in line of defense.…”
Section: Figure 6 Challenge Facing Information System Security Awaren...mentioning
confidence: 99%